Diversity of Santri Typology in Tahfidz House Education: Keberagaman Tipologi Santri dalam Pendidikan Rumah Tahfidz - Ade Ilfah; Syamsu Nahar; Azizah Hanum OK (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid growth of Rumah Tahfidz as non-formal Islamic educational institutions in Indonesia, especially in Medan, reflects increasing public interest in early religious education based on Qur’anic memorization. Specific Background: Despite the proliferation of these institutions, there is limited research focusing on the diversity of student characteristics, or tipologi santri, particularly in urban contexts like Medan. Knowledge Gap: Existing studies have largely emphasized teaching methods and institutional management, leaving a gap in understanding the classification and needs of students based on their socio-economic and motivational backgrounds. Aims: This study aims to identify and analyze the typologies of students in Rumah Tahfidz and examine the social, economic, and personal motivation factors influencing their learning profiles. Results: Using a qualitative multi-site approach at Daarul Uswah and Al-Munif, the research identified five main typologies: academic santri, fast memorizers, highly committed learners, progressing beginners, and socially driven religious santri, each with distinct characteristics and learning needs. Novelty: The study introduces a typological classification specific to urban Rumah Tahfidz settings and integrates sociological and educational theories to explain student diversity. Implications: Findings offer practical insights for tailoring Qur’anic memorization programs to student profiles, promoting more inclusive and effective pedagogical strategies in non-formal Islamic education.Highlight : Identifies diverse santri typologies shaped by social, economic, and motivational factors. Emphasizes the need for tailored educational strategies based on student characteristics. Highlights Rumah Tahfidz’s role in character building and non-formal Islamic learning. Keywords : Typology of Santri, Rumah Tahfidz, Islamic Education, Tahfidz Al-Qur'an, Medan City